Pemberdayaan Kelompok Masyarakat Desa Tawangargo Kabupaten Malang Melalui Pengembangan Produk Minuman Kesehatan - Pratiwi, Yunita Satya; Sholekhah, Nurul Niswatin; Tristanti, Dyah Ayu Lingling (Jurnal Ilmiah Pangabdhi, 2024)
Tawangargo Village is one of the villages in Malang Regency which is located in the highlands, where the area is suitable as a place for fruit and vegetable cultivation. However, fruit and vegetable crops are only sold without further processing. In fact, if processed properly, fruit and vegetable production will increase the economic value ofthe fruit and vegetables produced, for example the manufacture of fruit-based functional drinks. For this reason, Community Service activities are carried out using the method of delivering materials, processing, packaging processes, and product marketing strategies. This activity aims to increase public knowledge and interest in functional drinks and increase the use of fruits and vegetables in the Tawangargo area. In addition, the results of this community service activity can also become new jobs that can increase people's income, and can produce superior products that are distinctive and authentic and beneficial to health. It is hoped that in this activity the community will really apply the knowledge that has been conveyed.